CAISL: Simplification Logic for Conditional Attribute Implications - Mora-Bonilla, Ángel; Cordero-Ortega, Pablo; Enciso-García-Oliveros, Manuel; Rodríguez-Lorenzo, Estrella; Missaoui, Nokia (My University, 2016)
In this work, we present a sound and complete axiomatic system for conditional attribute implications (CAIs) in Triadic Concept Analysis (TCA). Our approach is strongly based on the Simplification paradigm which offers a more suitable way for automated reasoning than the one based on Armstrong’s Axioms. We also present an automated method to prove the derivability of a CAI from a set of CAI s.
Keywords: Axioma de elección; Triadic Concept Analysis; Logic; Implications